Data for: Prevalence and antimicrobial resistant Campylobacter spp. in broiler chicken carcasses and hygiene practises in informal urban markets in a low-income setting - Boqvist, Sofia; Erume, Joseph; Okello, Pius (Swedish University of Agricultural Sciences, 2025)
This project aimed to contribute to reduced spread of antimicrobial resistant (AMR) zoonotic bacteria in urban livestock production systems in low-income countries (LIC). This was done by providing new data on spread and diversity of antimicrobial resistant Campylobacter strains. Drivers to mitigate disease and reduce antimicrobial usage was also generated which will facilitate future initiatives for coordinated actions to reduce spread of AMR.

The project investigated the prevalence of Campylobacter on broiler chicken carcasses sold at informal markets around the capital Kampala in Uganda. Antimicrobial resistance of the isolated Campylobacter strains was analyzed against five different antibiotics: tetracycline, ciprofloxacin, streptomycin, erythromycin, and nalidixic acid. The data file contains 36 rows (Campylobacter strains) and 14 columns, and the data is explained in the documentation file "read_me_AMR_campylobacter."

The vendors selling the broiler chicken carcasses included in the study were interviewed orally using a questionnaire to gather information about their knowledge, practices, and routines related to food safety and food hygiene at the included markets. The data file contains 120 rows (respondents) and 41 columns (survey questions). The data is explained in the documentation file "read_me_food_safety_questionnaire_results."

Projektet syftade till att bidra till minskad spridning av antimikrobiellt resistenta (AMR) zoonotiska bakterier i urbana djurhållningssystem i låginkomstländer (LIC). Detta har gjorts genom att tillhandahålla ny data om spridning och diversitet av AMR Campylobacter-stammar. Faktorer för att minska sjukdomar och användningen av antimikrobiella medel kommer har också identifierats, vilket kommer att underlätta framtida initiativ för samordnade åtgärder för att minska spridningen av AMR.

I projektet undersöktes prevalensen av Campylobacter på slaktkycklingkroppar som såldes på informella marknader runt huvudstaden Kampala i Uganda. Antimikrobiell resistens mot de isolerade campylobactstammarna analyserades mot fem olika antibiotika; tetracycline, ciprofloxacin, streptomycin, erythromycin och nalidixic acid. Datafilen innehåller 36 rader (Campylobacter stammar) och 14 kolumner och data förklaras i dokumentationsfilen "read_me_AMR_campylobacter".

De försäljare som saluförde slaktkycklingkropparna, som ingick i studien, intervjuades muntligen utifrån ett frågeformulär för att få information kring kunskaper, tillämpning och rutiner kring livsmedelssäkerhet och livsmedelshygien på de inkluderade marknaderna. Datafilen innehåller 120 rader (respondenter) och 41 kolumner (enkätfrågor). Data förklaras i dokumentationsfilen "read_me_food_safety_questionnaire_results".
Data för: Prevalence and antimicrobial resistant Campylobacter spp. in broiler chicken carcasses and hygiene practises in informal urban markets in a low-income setting
Keywords: food safety; Campylobacter; Campylobacter; Campylobacter jejuni; Campylobacter jejuni; Campylobacter coli; Campylobacter coli; antimicrobial resistance; antimikrobiell resistens; campylobacter coli (doyle, 1948) veron & chatelain, 1973; campylobacter jejuni (jones et al., 1931) veron & chatelain, 1973; Microbiology; Mikrobiologi; Pathobiology; Patobiologi